MONITORAMENTO DOS NÍVEIS DE ATAQUE DE Sirex noctilio EM PLANTIOS DE Pinus taeda E EFICIÊNCIA DOS INIMIGOS NATURAIS - Carolo Junior, Silvio (2015)
The main damage caused to reforestation by insect pests are the breakdowns for forest planning and economic losses, and in pine plantations there is the plague Sirex noctilio (Hymenoptera: Siricidae). This study aimed to determine the natural dispersion and the efficiency of biological control agents Sirex noctilio. The experiment was installed in the city of Palmas - PR in two loblolly pine plantations, one with thinning (12 years -1051 trees/ha) Juca Fabricio`s farm and one without thinning (13 years -1600 trees / ha) Alegria`s farm. In each area were installed 05 groups of trees-trap. After inspection of the trees-trap, the attacked trees were cut into small logs of 1m length and stored in drums divided into two treatments with and without the application of nematode Deladenus siricidicola. To determine the percentage of attack were used three methods, namely: trees - trap, sequential sampling and census (1 ha). The nematode parasitism by D. siricidicola was 17.31% on the Alegria`s farm, being 15.28% in the treatment without application of nematode and 19.23% in the treatment with application of nematode. On the Juca Fabricio`s farm, the percentage of parasitism by nematodes was 37.78%, and the small logs that was not applied biological control parasitism was 40% and 33.33% in small logs that inoculation occurred. As for parasitism by Ibalia leucospoides it was 13.33% in Alegria`s farm and 8.16 on the Juca Fabricio`s farm. Alegria`s farm was found in 40% of trees attacked the trees-trap, 0.51% in the sequential sampling and 0.37% of attacked trees in the census. On the Juca Fabricio`s farm 28%, 0.15% and 0.21% of the trees were attacked-in the trees-trap, sequential sampling and census respectively. The methods tested for determining the presence of wood-wasp, trees-trap, sequential sampling and census proved satisfactory, with the census showed higher accuracy in the determination of the level of attack. The nematode Deladenus siricidicola is set out in two farms. The dispersion Deladenus siricidicola and Ibalia leucospoides occurred in areas of study.